Phytochemistry and biological activity of secondary metabolites : the phytochemistry and biological activity of secondary metabolites from Kenyan Vern - Kiplimo, Joyce; Koorbanally, Neil ([Place of publication not identifed] : Lap Lambert Academic Publishing, 2014)
This work is an account of the phytochemical analysis of two genera, Vernonia and Vepris which are used as remedies for illness by the Kalenjin community of Kenya.
Introduction -- Triterpenoids from Vernonia auriculifera Hiern exhibit antimicrobial activity -- A novel polyene from vernonia articifolia (Asteraceae) -- A novel flvonoid and furoqouinoline alkaloids from vepris glomerate and their antioxidant activity -- Ring A, D-Seco limonoids and flavonoids fro mteh Kenyan vepris uguenensis engl, and their antioxidant activity
Includes bibliographical references.
Keywords: PHYTOCHEMISTRY